Hubungan Beban Kerja Mental, Stres Kerja, dan Motivasi Terhadap Tingkat Konsentrasi Operator Crane Perusahaan Galangan Kapal - Pramesti, Rieke Hardita; Santiasih, Indri; Kusminah, Imah Luluk; Bimo Pratomo, Uranio Hario (Jurnal Teknologi Maritim, 2024)
Ship production activities at the Shipyard Company require lifting and transporting aircraft to facilitate work, one of which is a crane. Crane operators work monotonously at the wheel of the crane every day for 8 hours or even more. Concentration is needed in this job. Concentration is a state in which a person focuses his attention on an object within a certain time. Loss of concentration in the operator can lead to mismatches in work and the worst risk is the occurrence of work accidents. This study aims to determine the relationship between mental workload, work stress, and motivation with the level of concentration in crane operators. The population of this study were 35 crane operators. Sampling using total sampling technique with the entire population sampled. Measurements used the NASA-TLX questionnaire to measure mental workload, Stress Diagnosis Survey to measure work stress levels, motivation questionnaire and Grid Concentration Test to measure concentration levels. Data analysis using the chi square test, with the results showing that the independent variables that have a significance value <0.05 are mental workload with a value of 0.009 and work stress with a value of 0.044. While the motivation variable has a significance value of 0.391. The conclusion obtained is that the variables associated with the level of concentration are mental workload and work stress, while the motivation variable has no relationship with the level of concentration.